Typical dairy products in Africa from local animal resources. Issue 3 (3rd July 2018) - Mattiello, Silvana; Caroprese, Mariangela; Matteo, Crovetto Gianni; Fortina, Riccardo; Martini, Andrea; Martini, Mina; Parisi, Giuliana; Russo, Claudia; Zecchini, Massimo; ,
Abstract: Milk is recognised as an important element of the pastoral civilisations in Africa, where it has not only an economic value, but also a social and cultural value. The objective of this review is to identify the main African dairy products, mainly focussing on typical production processes based on the use of local animal resources. To this aim, dairy products were classified into five categories, according to the type and the production method: fresh cheese, ripened cheese, fermented milk, butter and dairy by-products. These categories give rise to an extraordinary range of local products where tradition, culture, and environmental conditions and constraints play a major role in contributing to this diversification. In some countries, some attempts are being made in order to valorise the local dairy products by establishing Slow Food Presidia or including them in the Ark of Taste compiled by Slow Food. One of the main constraints that limits the commercialisation and export of African dairy products is related to the scarce hygiene in milk production and processing, and the frequent absence of starter cultures, which result in products with non-standardised characteristics, short shelf life and high spoilage susceptibility, with consequent risks for human health. Efforts should be made to support the dairy products chain in Africa, by making production processes safer and by valuing local resources, in order to expand the internal market and the export opportunities. Development cooperation projects may play an important role in this respect and should therefore be encouraged.